Solar Thermoelectric Generator Prototype with Flat Black Color Coating on Copper Plate Heat Absorber - Purnama Putra, Fari Abid; Suprianto, Bambang (Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Surabaya, 2025)
Solar Thermoelectric Generators (STEGs) present a promising avenue for renewable energy production by converting solar heat into electricity. This study investigated the impact of a black coating on a copper heat absorber plate on STEG performance. A prototype incorporating eight TEG SP 1848-27145 SA modules connected in series was constructed for this experimental study. Copper plate temperature, voltage, and current were measured and analyzed using descriptive statistics and graphical representations. Results demonstrate that the black coating significantly elevated the copper plate temperature from 47.04°C to 49.14°C. This thermal enhancement led to improved thermoelectric performance, as evidenced by increased voltage from 5.54 V to 6.27 V and current from 50.64 mA to 63.73 mA. These findings confirm that a black coating on the copper heat absorber is an effective, low-cost strategy for enhancing the efficiency of solar-to-electric energy conversion in STEG prototypes.